Analisis Ekonomi Sektor Unggulan Di Kabupaten Nias Tahun 2012-2021. - Velix Eferli Halawa (JOURNAL ECONOMICS AND STRATEGY, 2023)
This study aims to analyze the potential sector typology and analyze the dominant growth sector in economic development in Nias Regency. For the purpose of analysis, secondary data was used in the form of a time series from 2012 to 2021, which were sourced from the Nias Regency BPS and North Sumatra Province BPS. The methods used include Klassen Typology analysis and Growth Ratio Model (MRP) analysis. The results of this study indicate that the sector with dominant growth is the Agriculture, Forestry and Fisheries Sector. Keywords: MRP, Klassen Typology.